Emergent approach to business resilience: a study of Ukrainian enterprises - Hrebeshkova, Olena; Kyzenko, Olena; Verba, Veronika (Business: Theory and Practice, 2025)
This study aims to profile the emergent behavioral responses of small and medium-sized enterprises (SMEs) in Ukraine to radical market changes and identify the cause-effect relationships that ensure their resilience through an emergent approach to strategic management. The article analyzes the results of a survey of 500 enterprises within the project “Advisory Support to SMEs in Ukraine Amid the Military Crisis”, implemented by CMC-Ukraine with support from Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ). Data were analyzed using MS Excel and RStudio. The study found that strategic decision-making profiles varied by sector. Grouping responses by functional areas (marketing, operations, finance, HR, digitalization) helped identify emergent strategy frameworks for different company clusters. These best practices were applied in the project “Access to Finance and Support for the Resilience of SMEs in Ukraine”, funded by Deutsche Sparkassenstiftung für Internationale Kooperation, which ran from February to August 2023.